2017
DOI: 10.3390/proteomes5010007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Al3+ and La3+ Trivalent Metal Ions on Tomato Fruit Proteomes

Abstract: The tomato (Solanum lycopersicum) ripening process from mature green (MG) to turning and then to red stages is accompanied by the occurrences of physiological and biochemical reactions, which ultimately result in the formation of the flavor, color and texture of ripe fruits. The two trivalent metal ions Al3+ and La3+ are known to induce different levels of phytotoxicity in suppressing root growth. This paper aims to understand the impacts of these two metal ions on tomato fruit proteomes. Tomato ‘Micro-Tom’ pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…114 Metal elements such as Al 3+ and La 3+ are able to induce some differential regulation of proteomic fluxes during the green, turning (breaker), and ripe stages of 'MicroTom' tomatoes, with greater influence on the biological activities of green stages. 88 Transcription factors modulate the development stages of fruit ripening by catalyzing the secondary metabolism. A recent study of the role of R2-R3MYB transcription factors in tomatoes reported their involvement in fruit setting from the period of anthesis.…”
Section: Proteomics Of Fruit Ripening and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…114 Metal elements such as Al 3+ and La 3+ are able to induce some differential regulation of proteomic fluxes during the green, turning (breaker), and ripe stages of 'MicroTom' tomatoes, with greater influence on the biological activities of green stages. 88 Transcription factors modulate the development stages of fruit ripening by catalyzing the secondary metabolism. A recent study of the role of R2-R3MYB transcription factors in tomatoes reported their involvement in fruit setting from the period of anthesis.…”
Section: Proteomics Of Fruit Ripening and Developmentmentioning
confidence: 99%
“…Some metalloproteases in tomato plants (Sl2-MMP and Sl3-MMP) were characterized to play roles in remodeling the cell wall structure in order to regulate cellular senescence and quick ripening of fruits . Metal elements such as Al 3+ and La 3+ are able to induce some differential regulation of proteomic fluxes during the green, turning (breaker), and ripe stages of ‘MicroTom’ tomatoes, with greater influence on the biological activities of green stages …”
Section: Proteomics Of Fruit Ripening and Developmentmentioning
confidence: 99%